Lexical competition in vowel articulation revisited: Vowel dispersion in the Easy/Hard database. (March 2015) - Gahl, Susanne
Abstract: A widely-cited study investigating effects of recognition difficulty on the phonetic realization of words (Wright, 2004 ). Factors of lexical competition in vowel articulation. In J. Local, R. Ogden & R. Temple (Eds.), Papers in laboratory phonology, Vol. VI (pp. 26–50)) reported that vowel dispersion, i.e. distance from the center of the talker's F1/F2 space, was greater in words that represented difficult recognition targets ('hard' words) than in easy recognition targets ('easy' words). The goal of the current study was to test whether that effect persisted when controlling for known other determinants of F1 and F2. A second goal was to test whether the pattern observed in the recordings analysed inWright (2004) extended to all monophthongs in the set of recordings of which the words analysed inWright (2004) formed a subset. We find that the dispersion difference between 'easy' and 'hard' words vowel dispersion is expected, given previous observations about effects of phonetic environment on vowel formants. When segmental context is taken into account, recognition difficulty fails to be predictive of vowel dispersion, both in the subset and in the larger database. An analysis of the fitted values of models of F1 and F2 based on consonantal factors (but not recognition difficulty) shows that the formant values predicted by those models separate vowels in "easy" and "hard" words in the manner observed in W2004. We discuss the implications for the effect of phonological neighbourhood density on language production, and for the relationship between lexical retrieval, auditory recognition difficulty and pronunciation variation.